Prophylactic use of interleukin 6 monoclonal antibody can reduce CRS response of CAR-T cell therapy - Dou, Baitao; Ren, Shihui; Qiu, Ling; Zhang, Xupai; Zhang, Nan; Cai, Jiao; Chen, Dan; Zhang, Qian; Yao, Hao; Fan, Fangyi (Frontiers in Medicine, 2024)
Chimeric antigen receptor T (CAR-T) cell immunotherapy is becoming one of the most promising treatments for hematological malignancies, however, complications such as cytokine release syndrome (CRS) seriously threaten the lives of patients. Interleukin 6(IL-6) monoclonal antibody is the common and useful treatment of CRS, however, it is not clear whether prophylactic use IL-6 monoclonal antibody can reduce the incidence of CRS. We searched the PubMed, Embase, web of Science, and Cochrane Library databases for studies that reported the prophylactic use of IL-6 monoclonal antibody in the treatment of CRS-related complications of CAR-T therapy before December 2022. The literature is screened according to the established inclusion and exclusion criteria, relevant data are extracted, and the quality of the literature is evaluated using the scale Cochrane bias risk assessment tool, and the Review Manager 5.3 is used to draw for related charts, use GetData2.20 software to extract the specific values of the data charts. The results shows that compared with no use of IL-6 monoclonal antibody to prevent CRS, IL-6 monoclonal antibody was given to patients at 8 mg/kg one hour before CAR-T cell infusion, which reduced the incidence of CRS [RR: 0.41 95 % confidence interval (0.20, 0.86) I[2]=0.0% P=0.338 z=-2.369 (p=0.018)]. In subgroup analysis, compared with those who did not use IL-6 monoclonal antibody to prevent CRS, IL-6 monoclonal antibody was given to patients at 8 mg/kg one hour before CAR-T cell infusion, which reduced lactate dehydrogenase (LDH )[MD:-617.21, 95% confidence interval (-1104.41,-130.01) I[2 ]=0% P=0.88 Z=2.48 (P=0.01)], prophylactic use of IL-6 monoclonal antibody has a significant effect on reducing C-reactive protein (CRP) after CAR-T therapy [MD:0.33 95% confidence interval (-3.38,4.04) I[2]=0.0% P=0.7 z=0.18(p = 0.86)], Ferritin [MD: -21498.06 95% confidence interval (-51785.27, 8789.15) I[2] = 33% P = 0.22 z = 1.39 (p = 0.16)] was not statistically significant. Conclusion: The prophylactic use of IL-6 monoclonal antibody can significantly reduce the incidence of CRS complications after CAR-T therapy, and can also reduce LDH after CAR-T therapy, but it is not effective for reducing the risk of CAR-T therapy. CRP and ferritin had no statistical significance.